2021
DOI: 10.2196/25750
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patterns of Healthy Aging Among Men Who Have Sex With Men: Protocol for an Observational Cohort Study

Abstract: Background With the graying of sexual and gender minority communities and the growing number of people aged ≥50 years living with HIV, it is increasingly important to understand resilience in the context of the psychosocial aspects of aging and aging well. Objective This paper aims to describe the methods and sample for the Understanding Patterns of Healthy Aging Among Men Who Have Sex With Men study. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 67 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The Healthy Aging substudy included six data collection waves at 6-month intervals from April 2016 to March 2019. Participants enrolled at their respective MACS sites after being screened by program staff (Egan et al, 2021). Participation eligibility included (a) being 40+ years old by the first data collection wave, (b) having attended one or more semiannual MACS visit in the 2 years prior to the first data collection wave, and (c) being a cisgender man who has had sex with a man since enrolling in the MACS.…”
Section: Methodsmentioning
confidence: 99%
“…The Healthy Aging substudy included six data collection waves at 6-month intervals from April 2016 to March 2019. Participants enrolled at their respective MACS sites after being screened by program staff (Egan et al, 2021). Participation eligibility included (a) being 40+ years old by the first data collection wave, (b) having attended one or more semiannual MACS visit in the 2 years prior to the first data collection wave, and (c) being a cisgender man who has had sex with a man since enrolling in the MACS.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis included SMM ( N = 1,071) who participated in visit 69 (2018–2019) of the MACS Healthy Aging substudy (Egan et al, 2021), when the ACP variables of focus were measured. All men provide informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for the study, participants had to be 40 years of age or older. Further details about the substudy can be found elsewhere [23]. A total of 1318 men participated in the Patterns of Healthy Aging Study between visits 66 (baseline) to 70 from October 2016 to March 2019.…”
Section: Methodsmentioning
confidence: 99%